Peningkatan Pengetahuan dan Keterampilan Ibu Menyusui melalui Demonstrasi Posisi dan Perlekatan Menyusui yang Benar di Wilayah Kerja Puskesmas Dolo Kabupaten Sigi - Ika Nurhaliza (Lembaga Pengembangan Kinerja Dosen, 2026)
Exclusive breastfeeding is an important way to improve infant health. However, successful breastfeeding is not only influenced by breast milk production but also by the mother's knowledge and skills in implementing the correct breastfeeding position and attachment. Incorrect position and attachment often cause various breastfeeding problems, such as sore nipples, low milk supply, pain during breastfeeding, and the baby not suckling effectively. This community service activity aims to improve the knowledge and skills of breastfeeding mothers through demonstrations of correct breastfeeding positions and attachments. The activity was held on Thursday, June 18, 2026, at the Maku Village Health Post, Dolo Community Health Center Work Area, Sigi Regency, targeting 6 breastfeeding mothers. The methods used included initial interviews, health education, demonstrations using baby props, hands-on practice by participants, discussions, and post-activity evaluations of knowledge and skills. Based on the results of the initial interviews, it was discovered that most mothers admitted to having experienced sore nipples and feeling low milk production, which led to fear when breastfeeding. After the demonstration, all participants showed high enthusiasm in practicing correct breastfeeding positions and attachments. The evaluation results showed an increase in participants' knowledge and skills. Five mothers (83.3%) had good knowledge and skills, while one mother (16.7%) had adequate knowledge and skills. This activity demonstrated that the demonstration method is an effective educational tool for improving mothers' breastfeeding skills, which is expected to support the success of exclusive breastfeeding.